Assessment of student concept maps on environmental pollution subjects during the pandemic covid-19 - Chandra Adi Prabowo; Sunarni Sunarni; Sri Widoretno; Puguh Karyanto; Bowo Sugiharto; Sri Dwiastuti (JURNAL BIOEDUKATIKA, 2022)
The ability to compile concept maps is strongly influenced by the knowledge possessed. This research aims to describe students' Concept Maps scores on environmental pollution during the Covid-19 pandemic. This research includes a quantitative descriptive using a survey method with a population of 210 high school students. Data collection uses a Google form that asks students to make Concept Maps at the end of learning environmental pollution material. The researcher then assesses and determines the score of each student. Student scores are then combined and an average is obtained. The results showed that the largest percentage was owned by a valid relationship component of 9.75%, followed by a hierarchical component with a percentage of 7.34% and a branching component with a percentage of 3.42%. The pattern component is the fourth component with a percentage of 1.31%, followed by an example component with a percentage of 1.30% and the last component is a crosslink with a percentage of 0%. Acquired student concept map scores can be used to assess student learning outcomes so it is hoped that this research can be an evaluation material for students and teachers.